PENERAPAN ASAS PROPORSIONALITAS PERJANJIAN PENGGUNAAN KARTU KREDIT DALAM SISTEM TRANSAKSI PERDAGANGAN - Junaidi Arif (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The purpose of this study to Assess setting rights and obligations of the parties tothe agreement of credit card usage in commercial transactions and reviewing theprinciples applied in the agreement proportionality independent merchantMandiri bank and consumer agreements with the credit card issuer bank.Normative research is that, with a conceptual approach (conceptual approach),approach to legislation, and historical approaches to achieve clarity and scientificjustification based on legal concepts that comes to the legal principles bydescribing the legislation as well as uncover the philosophical and mindset whogave birth to something that is being learned about the principle ofproportionality of credit card agreements in trade transactions. Study is a Primarylegal materials containing Legislation and Secondary Legal Materials withlibrary research (literature research).